The relationship of workload with nurses’ work stress at Kartini Hospital Lebak Regency year 2022 - Wiwin Kustina; Devi Silvyana Rosalia; Antonius Rino Vanchapo; Juan Seprianto Tusi; Eman Suban Lewar (Yayasan Pusat Pendidikan Vanchapo, 2023)
Background. Nurses are one of the health human resources that are considered for their existence in hospitals. However, the problem of HRK conditions is still an obstacle in hospitals. One of them is planning the number of nursing staff. If this is not addressed then the workload of nurses can increase and risk reducing the quality of service. In addition, in a company a workload that is too heavy can cause work stress. Research purposes. Describe the relationship between workload and work stress of nurses at Kartini Hospital, Lebak Regency in 2022. Research Methods. This type of research is a descriptive correlational quantitative research. The research approach used is cross sectional. The population in this study were all nurses who worked at Kartini Hospital with a total of 111 people. While the number of samples studied as many as 87 respondents with the data collection method is Consecutive Sampling. The data of this study used primary data by filling out a questionnaire. The collected data was then processed computerized and processed by the statistical technique of Kendall Tau correlation. Research results. The results showed that of the 87 respondents, most of them experienced a heavy workload, 41 (47.1%) respondents and 41 (47.1%) respondents experienced light work stress. The results of the Kendall's Tau statistical test showed that the p value = 0.006 which means it is smaller than 0.05 (p < ) so it can be concluded that there is a significant relationship between the workload and work stress of nurses with the Correlation Coefficient value of 0.271 which indicates the strength of the relationship. Workload with work stress is at a fairly strong level with a positive relationship direction. Conclusions and recommendations. There is a significant relationship between the workload and work stress of nurses with the strength of the work relationship at a fairly strong level. This research is expected to be input for hospitals in terms of planning the number of workers, especially nurses.